Urbanization of historical places: Case of As-Sela’ fortress - Gandah, Firas; Gandah, Firas; Al-Adayleh, Maysoleen; Sheikha, Omniya (project baikal, 2023)
Jordan is rich in valuable sites whose history goes back centuries. These objects attract wide attention not only at the local level, but also around the world. The city of Al-Tafilah in southern Jordan is one of such sites of exceptional historical, cultural and architectural significance. It is the place where one great, ancient, but little-known civilization of Nabatea was born. Currently, the uncontrolled process of rapid urbanization leads to infrastructural degradation, having a profound detrimental effect on historical and cultural monuments. The article considers as an example the fate of As-Sela’ fortress, one of the oldest monuments of Nabataean culture. The necessity of including As-Sela’ fortress in the broader economic and architectural system of the Al-Tafilah district is shown.